2016
DOI: 10.5507/bp.2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Short-term postoperative distress associated with open vs. transoral robotic surgery (TORS) in patients with T1-T2 carcinomas of the tongue base and supraglottis

Abstract: Background. This study compared the adverse effects of open surgery (OS) including lateral pharyngotomy and supraglottic laryngectomy vs. transoral robotic surgery (TORS) in the treatment of stage T1 and T2 carcinomas of the tongue base and supraglottis. Methods. A retrospective study involving a 49 (13 female and 36 male) patients with untreated T1 or T2 carcinomas. Twenty two were operated on using TORS and 27 underwent conventional OS. The indicators for comparison were: total blood loss during surgery, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
(16 reference statements)
2
29
0
1
Order By: Relevance
“…Steroids have been reported to reduce VAS pain scores and length of stay . Slama et al also investigated TORS for oral cancer and reported an average VAS of 5.1 for week 1, similar to our findings . Thiels et al reported a median prescription of 350 MME and use of 180 MME in TORS tonsillectomies (49% unused) compared to our mean prescription of 368 MME and use of 221 MME (40% unused) .…”
Section: Discussionsupporting
confidence: 87%
“…Steroids have been reported to reduce VAS pain scores and length of stay . Slama et al also investigated TORS for oral cancer and reported an average VAS of 5.1 for week 1, similar to our findings . Thiels et al reported a median prescription of 350 MME and use of 180 MME in TORS tonsillectomies (49% unused) compared to our mean prescription of 368 MME and use of 221 MME (40% unused) .…”
Section: Discussionsupporting
confidence: 87%
“…An initial assessment obtained 33 articles, of which 10 were selected that were potentially relevant after evaluating their abstracts ( 1 , 3 , 6 , 9 , 14 - 19 ). The full texts of those 10 articles were then obtained.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Four studies were cohort studies comparing TORS with other treatment approaches and modalities, including traditional surgical approaches and transoral laser microsurgery (TLM). [31][32][33][34] Population Characteristics…”
Section: Resultsmentioning
confidence: 99%
“…21 When comparisons were made between those who received TORS and those who received open surgery or CRT, the TORS group had higher QOL scores in several categories at various time points. 22,29,[31][32][33] Several but not all studies reported the lowest QOL scores at 3 months postoperatively and lower QOL scores in several categories among those who received adjuvant therapy after surgery. [17][18][19]21…”
Section: Quality Of Lifementioning
confidence: 99%